Study of Living Al-Qur'an: Reception Wirdus Sa'adah the Inner Obedience Fathul Ulum Islamic Boarding School - Hasan, Ubaidillah; Rodliyah, Lutfiatur (Universitas Nurul Jadid, 2023)
This study aims to explain the phenomenon of living Qur’an that occurs at Fathul Ulum Islamic Boarding School Kwagean Kediri related to the amaliyah tradition, it is Wirdus Sa’adah. The focus of this study is to find out the meaning of the amaliyah tradition, Wirdus Sa’adah, which is carried out after maktubah prayer by reading wirid of Surah Al-Fatihah 100 times a day. This study uses qualitative methods with data collection techniques in the form of observations, interviews, and documentation. The approach used is the phenomenology of social construction using the sociology of knowledge by Karl Mannheim and the social actions of Max Weber. The results of this study can be concluded that first, the activity of amaliyah tradition, Wirdus Sa’adah, is activity carried out individually or sirri means that are not required for everyone because it can interfere with the density of Islamic boarding school activities. Second, sociologically the meaning of the amaliyah tradition, Wirdus Sa’adah at Fathul Ulum Islamic Boarding School Kwagean, has an objective meaning, it means this tradition is a form of obedience to the teachings of kyai who as the model figures. This tradition expressively also affects the condition of religious psychological endurance that is good for practitioners and documentarily it is a local wisdom that needs to be preserved. Third, although Wirdus Sa’adah is not required by this Islamic boarding school, but most of the students followed the tradition with the motivation of expecting blessings from their readings.